Communicative cues and peaceful practices: Synthesizing historical and contemporary approaches to interfaith relations in India - Gupta, Gauri (Journal of Language, Literature, Social and Cultural Studies, 2025)
Interfaith conflict resolution is a field of study concerned with practices that create harmony between different religious groups during tense atmospheres. This paper focuses on communication cues of such practices that have facilitated interfaith relations in India. It uses historical case analysis to relook at peacebuilding efforts through the edicts of Emperor Ashoka, customs of the Middle Ages like the Ganga-Jamuni Tehzeeb, contemporary mohalla (neighbourhood) committees and youth interfaith initiatives. Findings show that the communication practices used in peacebuilding interventions, such as, creating safe spaces for the discussion of theological dialogue through debates, among others, become important reminders of how respect for other religious communities is created through dialogic exchange between those of different faiths. Across the case studies, communicative sentiments such as extending a hand of friendship, establishing direct and open communication, and entering sacred spaces as respectful guests emerge as important cues that create trust and mutual respect. Such exchanges show how dialogue is also seen in gestures and recurrent practices, which make space for grassroots initiatives and pluralism that become larger communicative responses to religious violence. The discussion shows that a system that ties together common moral values, shared cultural customs, inclusive education and channels of communication that debunk rumours is combative to religious animosity and hate speech. Based on such observations, the paper provides a novel approach combining interfaith discussions, collaborative community service initiatives and local peace committees with technology, hence synthesizing lessons from historical and contemporary approaches. The recommendations made in this paper are pertinent for legislators, educators and social studies scholars looking to work towards interfaith harmony.